O-103 The impact of the COVID-19 pandemic on infertility and endometriosis patients in the Netherlands: The use of telemedicine, quality of life and patient-centeredness. (6th August 2021) - Rosielle, K; Bergwerff, J; Schreurs, A; Knijnenburg, J; Bie, B. De; Maas, J; Nap, A; Van Wely, M; Lambalk, C; Goddijn, M; Custers, I; Van Loendersloot, L; et al.
Abstract: Study question: How do infertility patients, endometriosis patients and health care providers rate the virtual care that was provided during the first lockdown of the COVID-19 pandemic? Summary answer: Patients and health care providers rate telephone- and video consultations as good alternatives during the pandemic but it cannot replace future physical consultations. What is known already: Virtual alternatives to regular care such as telephone and video consultations are gaining more attention as replacement for physical consultations and are ideal for use in a social distancing situation as the COVID-19 pandemic. However, infertility and endometriosis patients often rely on physical consultations for reassurance as well as for treatments such as artificial reproductive technology and surgery. Not being able to receive these reassurances and treatments may cause stress especially as infertility patients are known to experience a high sense of urgency to obtain treatment. For patients with endometriosis, regular follow-up visits are important for continuity of care. Study design, size, duration: A cross-sectional cohort study was performed, including 555 patients and 101 health care providers in the field of infertility and endometriosis in the Netherlands. Online questionnaires were sent between May and October 2020. Participants/materials, setting, methods: Patients with infertility and endometriosis patients from a university hospital and members of the respective national patients organizations, as well as health care providers in the fields of infertility and endometriosis were asked to participate. The questionnaires consisted of demographics, appraisal of telephonic and video consultations (TCs and VCs) and assessment of fertility related quality of life (FertiQoL) and patient-centeredness of endometriosis care (ENDOCARE). Main results and the role of chance: The questionnaires were completed by 374 infertility patients, 181 endometriosis patients and 101 health care providers. 75.9% of the infertility patients, 64.8% of the endometriosis patients and 82.7% of the health care providers rated TCs as a good alternative for physical consultations during the COVID-19-pandemic. Only 21.3%, 14.8% and 21.3% rated TCs as a good replacement of physical consultations in general. 76.6% and 35.9% of the infertility and endometriosis patients reported to experience an increase in stress due to the altered care during the COVID-19 pandemic. 38.7% and 58.0% reported to have received sufficient information from their care givers. Infertility patients scored lower on the FertiQoL than the reference population, while the ENDOCARE results of endometriosis patients were comparable to the reference. Limitations, reasons for caution: This study was limited to the Dutch population. As the organization of infertility care varies internationally, the results will not be directly applicable to other countries or health care systems. Wider implications of the findings: Virtual care options are a good alternative for infertility and endometriosis patients in situations where physical consultations are not possible. Self-reported stress is especially high in infertility patients during the COVID-19-pandemic. Health care providers should provide more information to patients in order to increase their ability to cope with stress. Trial registration number: N/A